Ticlopidine induces embryonic development toxicity and hepatotoxicity in zebrafish by upregulating the oxidative stress signaling pathway - Xu, Rong; Xu, Pengxiang; Wei, Haiyan; Huang, Yong; Zhu, Xiaodan; Lin, Chuanming; Yan, Zhimin; Xin, Liuyan; Li, Lin; Lv, Weiming; Zeng, Shuqin; Tian, Guiyou; et al. (Ecotoxicology and environmental safety, 2023)
Ticlopidine exerts its anti-platelet effects mainly by antagonizing platelet p2y12 receptors. Previously, a few studies have shown that ticlopidine can induce liver injury, but the exact mechanism of hepatotoxicity remains unclear. Oxidative stress, metabolic disorders, hepatocyte apoptosis, lipid peroxidation, and inflammatory responses can all lead to hepatic liver damage, which can cause hepatotoxicity. In this study, in order to deeply explore the potential molecular mechanisms of ticlopidine -induced hepatotoxicity, we used zebrafish as a model organism to comprehensively evaluate the hepatotoxicity of ticlopidine and its associated mechanism. Three days post-fertilization, zebrafish larvae were exposed to varying concentrations (1.5, 1.75 and 2 μg/mL) of ticlopidine for 72 h, in contrast, adult zebrafish were exposed exposure to 4 μg/mL of ticlopidine for 28 days. Ticlopidine-exposed zebrafish larvae showed changes in liver morphology, shortened body length, and delayed development of the swim bladder development. Liver tissues of ticlopidine-exposed zebrafish larvae and adults stained with Hematoxylin & Eosin revealed vacuolization and increased cellular interstitial spaces in liver tissues. Furthermore, using Oil Red O and periodic acid-Schiff staining methods and evaluating different metabolic enzymes of ticlopidine-exposed zebrafish larvae and adults suggested abnormal liver metabolism and liver injury in both ticlopidine-exposed zebrafish larvae and adults. Ticlopidine also significantly elevated inflammation and oxidative stress and reduced hepatocyte proliferation. During the rescue intervention using N-acetylcysteine, we observed significant improvement in ticlopidine-induced morphological changes in the liver, shortened body length, delayed swim bladder development, and proliferation of liver tissues showed significant improvement. In conclusion, ticlopidine might inhibit normal development and liver proliferation in zebrafish by upregulation of oxidative stress levels, thus leading to embryonic developmental toxicity and hepatotoxicity. In this study, we used zebrafish as a model organism to elucidate the developmental toxicity and hepatotoxicity induced by ticlopidine upregulation of oxidative stress signaling pathway in zebrafish, providing a theoretical basis for clinical application. •The administration of Ticlopidine, a potent platelet aggregation inhibitor, induces hepatic injury.•Exposure to Ticlopidine leads to increased oxidative stress, associated with phenotypic changes observed in zebrafish.•Exposure to ticlopidine in zebrafish larvae led to reduced hepatic cellular proliferation.•Administration of the antioxidant N-acetylcysteine can rescue the adverse phenotype resulting from ticlopidine exposure.